Morphological Characteristics of Thousand‐Kilometer‐Scale Es Structures Over China. Issue 2 (20th February 2021) - Sun, Wenjie; Zhao, Xiukuan; Hu, Lianhuan; Yang, Sipeng; Xie, Haiyong; Chang, Shoumin; Ning, Baiqi; Li, Jianyong; Liu, Libo; Li, Guozhu
Abstract: Sporadic E (Es ) structures have been observed occasionally covering a large horizontal scale of more than 1, 000 km over China. Their onset locations and propagation features, and related generation mechanisms still remain unknown. In this study, a statistical analysis of large‐scale Es structures is performed based on the ionospheric total electron content obtained from ground‐based receiver networks, in combination with data from multiple ionosondes in China. The large‐scale strong Es structures mainly occur during summer months, with dominant horizontal azimuth in the east‐west and northwest‐southeast directions and dimensions of 1, 000–3, 000 km along the elongation. They predominantly drift southwestward at the speed of 30–210 m/s. The main onset region for the large‐scale Es structures over China is identified for the first time, which is around 20°–45°N and 100°–125°E. Based on the morphological features of large‐scale Es structures, and the observation of concurrent cases of traveling ionospheric disturbances, we surmise that gravity waves could play an important role in the generation of large‐scale Es structures. Plain Language Summary: The ionospheric sporadic E (Es ) layer, which is of high occurrence over mid‐to‐low latitude regions of China, was observed simultaneously or sequentially at locations separated by thousands of kilometers at times. Based on the traditional observational techniques, e.g., ionosonde, it is hard to determine whether the Es layers observed at different locations belong to the same structure with a large horizontal scale or belong to regional Es patches developed independently. In this regard, the ground‐based ionospheric total electron content measurements provide a good opportunity for characterizing large‐scale strong Es structures, which were observed to elongate up to more than 1, 000 km. Whereas the large‐scale Es structures have been reported occasionally, their general features and onset locations remain unclear. This constrains further understanding on the generation mechanism for large‐scale strong Es occurrence. In this study, a statistical analysis of occurrences and dynamics of large‐scale strong Es structures over China is performed. Most of the large‐scale strong Es structures were initially observed around 20°–45°N and 100°–125°E. It was suggested that gravity waves could play an important role in the initial generation of large‐scale strong Es structures. Key Points: A statistical analysis of large‐scale Es structures with horizontal scales of more than 1, 000 km over China is performed Most large‐scale strong Es structures initially appeared around 20–45°N and 100°–125°E and drifted southwestward Gravity waves were suggested to play an important role in driving the generation of large‐scale Es structures